Zooplankton Communities Associated With New and Regenerated Primary Production in the Atlantic Inflow North of Svalbard - Svensen, Camilla; Halvorsen, Elisabeth; Vernet, Maria; Franzè, Gayantonia; Dmoch, Katarzyna; Lavrentyev, Peter J.; Kwasniewski, Slawomir (Frontiers in Marine Science, 2019)
The Arctic Ocean is changing rapidly with respect to ice cover extent and volume, growth season duration and biological production. Zooplankton are important components in the arctic marine food web, and tightly coupled to the strong seasonality in primary production. In this study, we investigate zooplankton composition, including microzooplankton, copepod nauplii, as well as small and large copepod taxa, and primary productivity in the dynamic Atlantic water inflow area north of Svalbard in May and August 2014. We focus on seasonal differences in the zooplankton community and in primary productivity regimes. More specifically, we examine how a shift from “new” (nitrate based) spring bloom to a “regenerated” (ammonium based) post bloom primary production is reflected in the diversity, life history adaptations and productivity of the dominant zooplankton. North of Svalbard, the seasonal differences in planktonic communities were significant. In spring, the large copepod Calanus finmarchicus dominated, but the estimated production and ingestion rates were low compared to the total primary production. In summer, the zooplankton community was composed of microzooplankton and the small copepod Oithona similis. The zooplankton production and ingestion rates were high in summer, and probably depended heavily on the regenerated primary production associated with the microbial loop. There was clear alteration from dominance of calanoid copepod nauplii in spring to Oithona spp. nauplii in summer, which indicates different reproductive strategies of the dominating large and small copepod species. Our study confirms the dependence and tight coupling between the new (spring bloom) primary production and reproductive adaptations of C. glacialis and C. hyperboreus. In contrast, C. finmarchicus appears able to take advantage of the regenerated summer primary production, which allows it to reach the overwintering stage within one growth season in this region north of Svalbard. This suggests that C. finmarchicus will be able to profit from the predicted increased primary production in the Arctic, a strategy also recognized in small copepod species such as O. similis. We speculate that the ability of the copepod species to utilize the regenerated summer primary production and microbial food web may determine the winners and losers in the future Arctic Ocean.